2021
DOI: 10.3389/fpubh.2021.641673
|View full text |Cite
|
Sign up to set email alerts
|

On the Psychology of TikTok Use: A First Glimpse From Empirical Findings

Abstract: TikTok (in Chinese: DouYin; formerly known as musical.ly) currently represents one of the most successful Chinese social media applications in the world. Since its founding in September 2016, TikTok has seen widespread distribution, in particular, attracting young users to engage in viewing, creating, and commenting on “LipSync-Videos” on the app. Despite its success in terms of user numbers, psychological studies aiming at an understanding of TikTok use are scarce. This narrative review provides a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
2
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(148 citation statements)
references
References 54 publications
2
128
2
16
Order By: Relevance
“…TikTok has become one of the most popular applications in the world, boasting a young audience despite its Terms of Service stating users must be over the age of 13. TikTok is rampant among children and teenagers seeking to expand their social networks, seek fame, or express themselves creatively (Montag et al 2021). However, the application has a dark side, which puts its young users at risk.…”
Section: Tiktok: the Platform Audiences And Contentmentioning
confidence: 99%
“…TikTok has become one of the most popular applications in the world, boasting a young audience despite its Terms of Service stating users must be over the age of 13. TikTok is rampant among children and teenagers seeking to expand their social networks, seek fame, or express themselves creatively (Montag et al 2021). However, the application has a dark side, which puts its young users at risk.…”
Section: Tiktok: the Platform Audiences And Contentmentioning
confidence: 99%
“…According to a report at the end of 2020, the number of monthly active TikTok users worldwide was 800 million. About 81% of Chinese users were young people under 35 years old [15]. The gratification of entertainment is the main driver for TikTok users.…”
Section: Introduction 1internet Smartphone or Tiktok Use Disordermentioning
confidence: 99%
“…Of the 124 participants, 123 (99.2%) used IM apps and 67 (54%) used image-based SN apps. In turn, we found that no participants used the TikTok app; however, it should be noted that at the time data collection started for the present study, the TikTok app was called “musical.ly” [ 31 ], and was later renamed TikTok starting on November 2017. Further, only 3 participants reported using the Twitter app.…”
Section: Methodsmentioning
confidence: 95%